Geological context of the Boumnyebel talcschists (Cameroun) : Inferences on the Pan-African Belt of Central Africa - (:unkn) unknown (My University, 2010)
New field work and petrological studies in the Boumnyebel area has led us to redefine rock types and discuss their bearing on the evolution of the Pan-African fold belt of central Africa. Two units are distinguished. A Palaeoproterozoic unit consists of orthogneisses and amphibolites restricted to the south and southwest of the area studied. It is overlain by a Pan-African unit (nappe) comprised in its lower part of garnet micaschists associated with amphibolites, metagabbros, hornblendites and pyroxenites, and towards its top of garnet + kyanite micaschists locally associated with marble and amphibolites; talcschists occur as discontinuous ?30 m thick layers mainly above the lower micaschists. The rock types in the lower part of this nappe suggest active margin environments with detrital input from a nearby continental crust (arc or back-arc context), whereas in the upper part they rather suggest detrital input from a nearby continental crust submitted to erosion. Metamorphism in the Pan-African formations corresponds to amphibolite facies conditions, reaching anatexis to the NW of the area studied (migmatites). The metamorphic peak (syn-D2) is estimated at ~ 650-670°C / ~ 9.5 kbar at ca. 620 Ma (monazite Th-U-Pb data), and the isograds are in normal positions. These data suggest that the thermal peak postdate nappe emplacement. We emphasize that the presence in significant proportions of mafic and ultramafic rocks of tholeiitic affinity in the lower part of the series suggests the existence of an active margin to the North of the Congo craton during the Neoproterozoic.
Keywords: African Research